Strategies for employees to effect change to improve performance of public organizations - Nasamu, Ibrahim (Journal of Accounting, Business and Finance Research, 2023)
Seventy percent of organizations fail in their organizational change initiatives because of failure to involve employees in the change process. Some managers lack the strategies to implement change initiatives successfully. Using Kotter’s eight-step change model as the conceptual framework, this qualitative case study was conducted to explore public sector managers’ strategies to include employees in implementing organizational change. Semi-structured interviews were used to identify public sector managers’ strategies that include employees in implementing organizational change. Interviews were conducted with eight participants who met the inclusion criteria for this study. Data analysis included methodological triangulation and Yin’s five-phase data analysis. The five resulting principal themes are effective communication, creating and sustaining employee engagement, leadership style effect, developing training programs and processes, and strengthening organizational culture. The findings indicate that managers should focus on how well their subordinates understand the overarching goals of the vision and mission of change initiatives. These findings have potential implications for positive social change that include catalyzing employees to have a healthier attitude at work, have a better sense of work–life balance, and have a sense of belonging. Understanding the contribution of an engaging workforce may enable organizations to improve performance and profits by catalyzing monetary and non-monetary contributions to benefit citizens.